Annual Report 2001 - Multilateral Investment Guarantee Agency (Washington, DC: World Bank, 2013)
The report discusses the Multilateral Investment Guarantee Agency's (MIGA) activities for the fiscal year ended June 30, 2001. Highlights discussed in this report include: 1) country membership; 2) guarantee operations; 3) MIGA's financial statements; and, 4) technical assistance services, including strategic planning, and training, privatization, business opportunities, and information technology. It also expands on MIGA's focus in producing results, in developing investment marketing services, pioneering new insurance tools for entering new markets, and in promoting new partnerships. The guarantees program, legal and policy framework, are largely described, to finally provide a financial overview, and its financial statements.